Health Care Utilization Patterns for Patients With a History of Substance Use Requiring OPAT. (5th November 2021) - Ashraf, Bilal; Hoff, Emily; Brown, L Steven; Smartt, Jillian; Mathew, Sheryl; Bird, Cylaina; Collins, Ryan; Johnson, David; Marambage, Kapila; Bhavan, Kavita
Abstract: Background: Uninsured people who use drugs (PWUD) require extended parenteral antibiotic therapy when diagnosed with complex infections such as osteomyelitis. They are ineligible to enroll in our self-administered outpatient antimicrobial therapy (S-OPAT) program and instead sent to a skilled nursing facility (SNF). We aim to retrospectively assess clinical outcomes of PWUD discharged from our safety net hospital to complete OPAT in an SNF. Methods: Using our hospital electronic medical record, PWUD discharged to an SNF for extended antibiotic therapy were identified for the study period, 1/1/17–4/30/18. Demographics, drug use, discharge diagnosis, antibiotic therapy, discharge disposition from SNF (AMA, early non-AMA, completed), 30-day emergency department (ED) utilization, and 30-day readmission were collected for the study cohort. ED utilization and 30-day readmission rates were analyzed by disposition group. Results: While the majority of patients completed treatment (83), a sizeable number left AMA (26) or early non-AMA (20). Patients who left early, AMA or non-AMA, had increased rates of 30-day readmission or ED utilization ( P =.01) and increased rates of 30-day readmission alone ( P =.01), but not ED utilization alone ( P =.43), compared with patients who completed treatment. Conclusions: In our cohort, many PWUD discharged to an SNF to receive parenteral antibiotics did not complete treatment. These patients were observed to have increased health care utilization compared with patients completing therapy.